The Monastic Journey of St. Josaphat Kuntsevych: Byzantine Traditions and Spiritual Parallels with the Saints of the Kyiv Pechersk Lavra - Kirkienė, Genutė (Lietuvos istorijos studijos, 2025)
The article aims to explore the monastic journey of St. Josaphat Kuntsevych, beginning with his family background and continuing with his monastic life at the Basilian Monastery of the Holy Trinity in Vilnius. The article also explores how the religious literature of that time may have influenced Josaphat’s spiritual beliefs and his decision to pursue the monastic path. Special attention is given to the traditions of the Byzantine Church Fathers and the local Kyiv-Pechersk Paterikon, which shaped the spiritual practices reflected in Josaphat’s life, as analysed through his ascetic and spiritual disciplines.